THE INFLUENCE OF WORK DISCIPLINE AND PROFESSIONALISM ON QUALITY OF PUBLIC SERVICES IN BANDAR VILLAGE OFFICE CENTRAL, KEC. KHALIPAH BANDAR, REGENCY. SERANG DIFFERENT (Case Study of the Community of Bandar Tengah Village, Kec, Bandar Khalipah, Serdang Bedag - CAI CEN, CIA (Universitas Efarina, 2020)
This study aims to determine the Influence of Work Discipline, and Professionalism on the Quality of Public Services at the Bandar Tengah Village Office, Bandar Khalipah District, Serdang Bedagai Regency (Case Study of the Bandar Tengah Village Community, Bandar Kalipah District, Serdang Bedagai Regency ). This type of research is a quantitative method approach and obtains data by distributing questionnaires to respondents who are used as samples for this study and then the data is processed using SPSS (Staticical Product and Service Solution) Version 25.00. This study used a sample of 100 respondents, this study involved 100 people who came to the bandartengah village office. Sampling using the Random Sampling technique. From the results of this test, it can be concluded that the first hypothesis is accepted, that is, the variable of work discipline (X1) has a significant effect on the variable of quality of public services (Y). Hypothesis 2 can be concluded that the second hypothesis is accepted that is to say, the variable of professionalism (X2) has a significant effect on the variable of quality of public services (Y). And it can be concluded that the third hypothesis is accepted, meaning that the variable of labor discipline (X1), the variable of professionalism (X2) affects jointly (simultaneously) the variable of quality of public services (Y).